The Effect of Transformational Leadership and Work Motivation on Performance through Employee Satisfaction - Mahdalena; Malik, Nazaruddin; Mohyi, Achmad (University of Muhammadiyah Malang, 2022)
Jawa Timur Park 1 or better known as Jatim Park 1 is a place for recreation and learning established by PT. Bunga Wangsa Sejati which has been open since 2001. Jatim Park 1 which was established in Batu City, East Java is one of the famous Batu City tourist destinations. As an industry and of course, the quality of Jawa Timur Park 1 services is highly valued not only from the rides offered, but also from the service of the employees who are kept. The purpose of the discussion in this research is to determine the effect of transformational leadership and work motivation on performance through job satisfaction. The data collection method in this study used a questionnaire with data analysis techniques using SmartPLS. The results show that transformational leadership and work motivation affect employee performance, and job satisfaction mediates the effect of transformational leadership and work motivation on employee performance.